Cardiac magnetic resonance outperforms echocardiography to predict subsequent implantable cardioverter defibrillator therapies in ST-segment elevation myocardial infarction patients - Marcos-Garcés, Víctor; Perez, Nerea; Gavara, Jose; Lopez-Lereu, Maria P.; Monmeneu, Jose V.; Rios-Navarro, Cesar; de Dios, Elena; Merenciano-González, Hector; Gabaldon-Pérez, Ana; Ferrero-De-Loma-Osorio, Ángel; Martínez-Brotons, Ángel; Bondanza, Lourdes; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Implantable cardioverter defibrillators (ICD) are effective as a primary prevention measure of ventricular tachyarrhythmias in patients with ST-segment elevation myocardial infarction (STEMI) and depressed left ventricular ejection fraction (LVEF). The implications of using cardiac magnetic resonance (CMR) instead of echocardiography (Echo) to assess LVEF prior to the indication of ICD in this setting are unknown. Materials and methods We evaluated 52 STEMI patients (56.6 ± 11 years, 88.5% male) treated with ICD in primary prevention who underwent echocardiography and CMR prior to ICD implantation. ICD implantation was indicated based on the presence of heart failure and depressed LVEF (≤ 35%) by echocardiography, CMR, or both. Prediction of ICD therapies (ICD-T) during follow-up by echocardiography and CMR before ICD implantation was assessed. Results Compared to echocardiography, LVEF was lower by cardiac CMR (30.2 ± 9% vs. 37.4 ± 7.6%, p < 0.001). LVEF ≤ 35% was detected in 24 patients (46.2%) by Echo and in 42 (80.7%) by CMR. During a mean follow-up of 6.1 ± 4.2 years, 10 patients received appropriate ICD-T (3.16 ICD-T per 100 person-years): 5 direct shocks to treat very fast ventricular tachycardia or ventricular fibrillation, 3 effective antitachycardia pacing (ATP) for treatment of ventricular tachycardia, and 2 ineffective ATP followed by shock to treat ventricular tachycardia. Echo-LVEF ≤ 35% correctly predicted ICD-T in 4/10 (40%) patients and CMR-LVEF ≤ 35% in 10/10 (100%) patients. CMR-LVEF improved on Echo-LVEF for predicting ICD-T (area under the curve: 0.76 vs. 0.48, p = 0.04). Conclusion In STEMI patients treated with ICD, assessment of LVEF by CMR outperforms Echo-LVEF to predict the subsequent use of appropriate ICD therapies.